PLURALISME DAN DIALOG ANTARUMAT BERAGAMA - M. Zainuddin (Litbang STFT Widya Sasana Malang, 2005)
Religious pluralism is undeniable phenomenon. Religion always emerges in a plural context. Whenever pluralism is not faced in a right way, there will be fierce conflict. It has oftentime happened to monotheistic religions. To prevent conflicts we have to search better approaches. This article intends to highlight problem of religious pluralism and to analyze approaches provided by some scholars, such as John Hick, Brian Fay, Schuon and Hossein Nasr. Analysis goes to achieve some concluding remarks for better interreligious dialogues in Indonesia.